PELATIHAN PENYUSUNAN INSTRUMEN EVALUASI BERBASIS HIGHER ORDER THINKING SKILLS (HOTs) UNTUK GURU MI DI KEBUMEN - Siti Fatimah; Atim Rinawati (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
This service aims to provide training on the preparation of HOTs-based evaluation instruments to madrasah ibtidaiyah teachers in Kebumen. This service is located at MI Ma'arif Jatimulyo. This activity was attended by three madrasah in Kebumen who were members of a teacher working group, namely MI Ma'arif Jatimulyo, MI Al-Hidayah Karangtanjung, MI Nurussulaiman Seliling. This service activity consists of four stages, which consist of planning, preparation, implementation, and evaluation. The results of the analysis showed that the participants had very good results with a percentage of 98.61%. This was marked by the participants' understanding of the importance of excellent HOTs and the results of the questions presented by participants that were in accordance with the standards for preparing HOTs-based instruments. In addition, it was found that 100% of the participants stated that this activity was very helpful in developing the competence of madrasah ibtidaiyah teachers.